2004
DOI: 10.1111/j.1651-2227.2004.tb03032.x
|View full text |Cite
|
Sign up to set email alerts
|

New findings in partial trisomy 16q: clinical report

Abstract: Based on this clinical report, megalocornea, partial callosal agenesis and mild bilateral occipital lobe hypoplasia should perhaps be included in the list of anomalies associated with partial trisomy 16q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
3
13
0
Order By: Relevance
“…In the literature, two other patients with partial 11q monosomy and partial 16q trisomy were reported [Sousa et al, 2004;Zahn et al, 2005]. In both cases, children shared clinical features with ours (Table I).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In the literature, two other patients with partial 11q monosomy and partial 16q trisomy were reported [Sousa et al, 2004;Zahn et al, 2005]. In both cases, children shared clinical features with ours (Table I).…”
Section: Discussionsupporting
confidence: 66%
“…Patient 3, who had a smaller 11q monosomy, had no thrombocytopenia or hemorrhage, as patients with similar 11q monosomy reported in the literature [Schultz et al, 2001;Megarbane et al, 2002;Sousa et al, 2004;Keppler-Noreuil et al, 2007]. Thrombocytopenia was reported in 56% of patients with a subtelomeric 11q deletion [Courtens et al, 2007], but Grossfeld et al reported that 94% of patients with Jacobsen syndrome (without size deletion precision) had a history of thrombocytopenia.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Thus, we compared our clinical findings with those described typically in terminal deletions of 11q [Lewanda et al, 1995;Penny et al, 1995; Pivnick et al, 1996;Grossfeld et al, 2004] as well as with those reported in four cases of cryptic or subtle duplications of 16q24 [Giardino et al, 2001;Baker et al, 2002;Brisset et al, 2002]. Additionally, a patient reported by Sousa et al [2004] was included in the comparison because her phenotype is caused by partial monosomy 11q (11q25-qter, smaller than in our patients) and a partial trisomy 16q (16q22-qter, larger than in our patients). The comparison of clinical findings is summarized in Table II.…”
Section: Discussionmentioning
confidence: 82%